Esterification of oleic acid with etanol by using sulfated zirconia catalyst in the presence of triglycerides : kinetic and modeling study - Abdul Rafiq, Mohamad Yazid (2009)
This dissertation is about the esterification of oleic acid with ethanol by using sulfated zirconia as a catalyst in the presence of triglycerides. In this dissertation the kinetic and the modeling study about the reaction as well as the best operating parameter for the reaction will be studied and investigated. Biodiesel is the one the new possible substitute of regular fuel for engines and it can be produced from various animal fats and vegetable oils. The biodiesel has more advantages compared to the fossil based fuel because it has lower emission of carbon monoxide due to the better combustion, a better lubricating effect on engines, non sulfur emission and non particulate matter pollutant. In this study, there are four operating parameter were investigated and studied which are temperature, amount of catalyst, ratio of oleic acid to the ethanol and the addition of triglycerides. The best operating condition in this study has been produced 31.7% final conversion of oleic acid. The experimental data have been interpreted with pseudo-homogenous kinetic model and the rate constant has been determined from the calculation. It was found out that the sulfated zirconia catalyst was suitable to perform not only esterification reaction but also the tranesterification reaction in biodiesel production.